KAJIAN LITERATUR: PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DALAM PENINGKATAN KEMAMPUAN NUMERASI DI SD - Firza, Muhammad; Evi Maulidia Lestari; Putri Sardela; Tiara Nur Asyifa; Ahmad Suriansyah; Wahdah Refia Rafianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Systematic Literature Review aims to examine the effectiveness of the Realistic Mathematics Education (RME) approach in enhancing numeracy skills among Elementary School (ES) students. The study is motivated by the low global numeracy literacy of Indonesian students and the dominance of conventional mathematics teaching methods. The method employed is a Systematic Literature Review (SLR), analyzing empirical research journals concerning RME and numeracy in ES published from 2018–2025. The synthesis results demonstrate that applying RME has a significant impact on improving students' numeracy literacy compared to conventional methods. RME is proven effective because it begins learning from realistic contexts, promotes active student involvement in guided reinvention, and links abstract concepts to daily life experiences. This improvement covers the ability to understand problem context, mathematical reasoning, and solving real-life problems. This review concludes that RME is a systematic and relevant learning strategy for strengthening ES students' numeracy, aligned with the demands of the Merdeka Curriculum.